2007
DOI: 10.1038/sj.bmt.1705648
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte reconstitution following allogeneic hematopoietic stem cell transplantation: a retrospective study including 148 patients

Abstract: Here we investigated the influence of parameters known before hematopoietic stem cell transplantation (HSCT) as well as the relevance of graft-versus-host disease (GvHD) and cytomegalovirus (CMV) reactivation on post transplant lymphocyte reconstitution in 148 patients treated in our institution between 1996 and 2003. Median patient age was 42 (19-68) years, HSCT followed standard high dose (n ¼ 91) or reduced-intensity conditioning regimens (n ¼ 57) with bone marrow (BM, n ¼ 67) or peripheral blood stem cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 42 publications
4
45
1
Order By: Relevance
“…Peripheral blood-derived grafts, as opposed to BMderived grafts, have been shown to be advantageous in terms of a faster hematopoietic and immune reconstitution. 30 Furthermore, although not statistically significant, Ringden et al 29 observed a higher RFS in unrelated recipients compared with related HCT in patients with acute GVHD in contrast to patients without acute GvHD. In addition, in that study, NRM accounts for more deaths than does disease relapse, and unrelated recipients had a higher NRM than related transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood-derived grafts, as opposed to BMderived grafts, have been shown to be advantageous in terms of a faster hematopoietic and immune reconstitution. 30 Furthermore, although not statistically significant, Ringden et al 29 observed a higher RFS in unrelated recipients compared with related HCT in patients with acute GVHD in contrast to patients without acute GvHD. In addition, in that study, NRM accounts for more deaths than does disease relapse, and unrelated recipients had a higher NRM than related transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…4 Other studies have not demonstrated significantly improved immune reconstitution with RIC, 5,6 making this area a subject of continued debate (reviewed by Jimenez et al 7 ). While many previous studies of immune reconstitution post HSCT have focused on lymphocyte subset recovery, [8][9][10][11][12][13][14][15][16] we have previously shown that combined monocyte and lymphocyte recovery also has an impact on survival post myeloablative HSCT in acute leukemia due to a reduction in nonrelapse mortality. 17 Here, we test the hypothesis that both lymphocyte and monocyte recovery are similarly associated with survival in patients undergoing RIC allogeneic HSCT with fludarabine and melphalan.…”
Section: Introductionmentioning
confidence: 99%
“…26 Thus, we hypothesize that this reaction occurred by the regeneration of CD4 þ T cell, provided that in the setting of SCT the regeneration of this subset of cells generally occurs between 6 and 12 months after the transplantation. 22 This clinical and immunological picture may be similar to a new clinical syndrome known as immune reconstitution inflammatory syndrome (IRIS) 27 observed in HIV-infected patients receiving highly active antiretroviral therapy. Those patients exhibit paradoxical deterioration in their clinical status, generally induced by exuberant inflammatory responses toward opportunistic pathogens and often associated with a rapid increase in CD4 lymphocyte count after satisfactory control of viral replication.…”
Section: Discussionmentioning
confidence: 95%
“…CD4 þ T cells regenerate later and only 21% of the patients reach normal counts within the first year. 22 The situation after allogeneic HSCT mimics that of severe combined immunodeficient (SCID) mice, which are increasingly susceptible to leprosy 23,24 and clear the infection when reconstituted with BM cells from immunocompetent mice. 25 We hypothesized that the severity of the immunosupression that occurs in the context of the SCT, specifically the delayed normalization of CD4 þ T cells, may explain the opportunistic infections in cases 1-3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation